The Effect of Access Cavity Preparation, Canal Shaping and Pericervical Dentine Preservation on the Fracture Resistance of Endodontically Treated Mandibular Molars - Vorster, Martin (My University, 2022)
Fracture resistance remains a great concern when evaluating long-term success after endodontic treatment of human teeth. Structural integrity is one of the main factors impacting the fracture resistance and longevity of endodontically treated teeth. Access cavities and canal preparations should aid in direct access into the root canal system without compromising the conservation of tooth structure. Pericervical dentine and the structural integrity thereof is described in the international literature as a key factor in the long-term prognosis of endodontically teeth with specific reference to fracture resistance. The preservation of dental hard tissue has also been shown to significantly reduce stress concentrations, especially in the cervical region of the tooth, and to increase the resistance to fracture after endodontic treatment of these teeth. In this study the effect of different endodontic access cavity preparations in combination with WaveOne Gold and TruNatomy on remaining pericervical dentine and preparation times were evaluated. The effect of remaining pericervical dentine thickness and volume in combination with different access cavity designs on the fracture resistance was further evaluated in extracted human mandibular first molars. The study was conducted over two phases: Phase 1: Sixty, extracted, human first mandibular molars were scanned using micro-CT. Minimum remaining pericervical dentine thickness and volume was measured and recorded after which two different types of access cavities were prepared: a traditional access cavity and a conservative access cavity. Teeth were randomly divided within the two different “access cavity groups” into two canal preparation groups. Root canals were then prepared using two different popular single-file preparation systems after which teeth were again scanned using micro-CT. Remaining pericervical dentine (thickness and volume) was again measured post-operatively and compared to preoperative measurements. Preparation times were also recorded between these four groups to evaluate the effect of different parameters on canal preparation time. The results of this phase showed significantly reduced preparation times in samples prepared with conservative access cavities compared to traditional access cavities. Remaining dentine thickness and volume was significantly reduced in the traditional endodontic access cavity preparation groups. The instrumentation system didn’t affect remaining dentine thickness, volume or preparation times significantly within the same endodontic access cavity preparation groups. Phase 2: Fracture resistance tests were conducted using nonlinear Finite Element Analysis (FEA). This was done in order to evaluate the effect different access cavity preparations have on the overall tooth structural capacity, taking also into account the different canal shaping instrumentation systems. The effect of preservation of pericervical dentine volume and thickness on the fracture resistance of endodontically treated mandibular molars were therefore evaluated. The nonlinear analysis of three-dimensional (3D) models accounted for material nonlinearities and simulated the crack opening phenomenon. The result of this phase suggests that fracture resistance is significantly reduced in mandibular first molars with traditional endodontic access cavities compared to those with conservative endodontic access cavity preparation. Within the limitations of this current study, the instrumentation system didn’t show a significant effect on fracture resistance within the same endodontic access cavity preparation groups. It is therefore suggested that the preservation of dentine and more specifically, pericervical dentine has a significant influence on fracture resistance in mandibular first molars.
Keywords: Conservative Endodontic Access; Fracture resistance; Finite Element Analysis; Traditional Endodontic Access; Pericervical Dentine; Preparation time